2002
DOI: 10.1051/forest:2002062
|View full text |Cite
|
Sign up to set email alerts
|

Beech (Fagus sylvatica L.) branches show acclimation of xylem anatomy and hydraulic properties to increased light after thinning

Abstract: -Hydraulic acclimation of Fagus sylvatica L. was analysed in response to forest thinning. Several months after thinning, leaf and xylem water potential and stomatal conductance of thinned branches were compared to sun-exposed and shade branches. We characterised vulnerability to cavitation for branches taken from these three treatments. We compared effect of thinning on xylem anatomy (mean vessel diameter, vessel density). Thinned branches exhibited higher stomatal conductance and lower leaf water potential. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 33 publications
8
36
0
Order By: Relevance
“…A similar result was found in Fagus sylvatica L., which avoided leaf wilting under full-sunlight conditions after shading. This temperate woody plant also decreased hydraulic resistance of branch by thinning, which is the same as full sunlight exposure after long shading (Lemoine et al, 2002). These results suggested that the fl exibility of R of stem was a powerful factor that kept leaf growth and biomass production under the variable light intensity condition.…”
supporting
confidence: 49%
“…A similar result was found in Fagus sylvatica L., which avoided leaf wilting under full-sunlight conditions after shading. This temperate woody plant also decreased hydraulic resistance of branch by thinning, which is the same as full sunlight exposure after long shading (Lemoine et al, 2002). These results suggested that the fl exibility of R of stem was a powerful factor that kept leaf growth and biomass production under the variable light intensity condition.…”
supporting
confidence: 49%
“…Increased irradiation of canopy tree leaves due to wilting of liana leaves following cutting would result in greater evaporative demand (Nobel 1983), and would contribute to greater transpiration and sap velocity. The v www.esajournals.org observed increase in sap velocity also suggests that canopy trees released from liana competition will increase photosynthetic carbon uptake once leaves and branches acclimate to higher irradiation (Kursar and Coley 1999, Lemoine et al 2002, Guo et al 2006.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to biotic factors such as pathogens and insects, two physiological (2011-2040, 2036-2065 and 2066-2095), respectively. Green colour represents areas modelled as suitable for beech at the given period 206 E. Rasztovits et al mechanisms have been proposed in the literature as potential causes of mortality: (1) embolism happens rapidly when soil water potential drops below a threshold value and if there is no efficient stomatal limitation of water losses (Lemoine et al 2002), and (2) the C starvation hypothesis predicts that reduced C assimilation caused by drought-induced stomatal closure leads to an imbalance between C availability and C loss. Over time, if drought persists, such negative C balance can lead to an exhaustion of C reserves and, ultimately, to death.…”
Section: Performance Of the Edmmentioning
confidence: 99%